CLINICAL FEATURES OF GASTROINTESTINAL TRACT LESIONS IN PATIENTS WITH SYSTEMIC LUPUS ERYTHEMATOSUS - Iskanova, Gulshan; Egamova, Sayyora; Israilova, Nigora (Medical science of Uzbekistan, 2025)
Relevance. Systemic lupus erythematosus is a common disease among rheumatic diseases of childhood. The frequency of the disease has a steady upward trend due to changes in the environment and eating disorders. The aim of the study was to evaluate the expected effect of antiulcer therapy with histamine H2-receptor blockers on the condition of the gastric mucosa in patients taking GCS for a long time. Materials and methods of research. The study prospectively evaluated the effect of antiulcer therapy on the morphological picture of the stomach in 56 patients with SLE who had been continuously taking corticosteroids for a long time. The results of the study. The positive effect of successful ranitidine therapy on the condition of the gastric mucosa was observed in patients with SLE who had been continuously using GCS for a long time and continued to take these drugs. Conclusion. A prospective assessment of the morphological effects of anti-ulcer therapy in patients with SLE who had been using corticosteroids for a long time and continued to take them showed a statistically significant positive trend in the morphological parameters of the antrum and fundus of the stomach.